Co‐targeting bromodomain and extra‐terminal proteins and MCL1 induces synergistic cell death in melanoma. Issue 8 (24th April 2020) - Tseng, Hsin‐Yi; Dreyer, Jan; Emran, Abdullah Al; Gunatilake, Dilini; Pirozyan, Mehdi; Cullinane, Carleen; Dutton‐Regester, Ken; Rizos, Helen; Hayward, Nicholas K.; McArthur, Grant; Hersey, Peter; Tiffen, Jessamy; et al.
Abstract: The treatment of melanoma has been markedly improved by the introduction of targeted therapies and checkpoint blockade immunotherapy. Unfortunately, resistance to these therapies remains a limitation. Novel anticancer therapeutics targeting the MCL1 anti‐apoptotic protein have shown impressive responses in haematological cancers but are yet to be evaluated in melanoma. To assess the sensitivity of melanoma to new MCL1 inhibitors, we measured the response of 51 melanoma cell lines to the novel MCL1 inhibitor, S63845. Additionally, we assessed combination of this drug with inhibitors of the bromodomain and extra‐terminal (BET) protein family of epigenetic readers, which we postulated would assist MCL1 inhibition by downregulating anti‐apoptotic targets regulated by NF‐kB such as BCLXL, BCL2A1 and XIAP, and by upregulating pro‐apoptotic proteins including BIM and NOXA. Only 14% of melanoma cell lines showed sensitivity to S63845, however, combination of S63845 and I‐BET151 induced highly synergistic apoptotic cell death in all melanoma lines tested and in an in vivo xenograft model. Cell death was dependent on caspases and BAX/BAK. Although the combination of drugs increased the BH3‐only protein, BIM, and downregulated anti‐apoptotic proteins such as BCL2A1, the importance of these proteins in inducing cell death varied between cell lines. ABT‐199 or ABT‐263 inhibitors against BCL2 or BCL2 and BCLXL, respectively, induced further cell death when combined with S63845 and I‐BET151. The combination of MCL1 and BET inhibition appears to be a promising therapeutic approach for metastatic melanoma, and presents opportunities to add further BCL2 family inhibitors to overcome treatment resistance. Abstract : What's new? Inducing apoptosis in melanoma has proven difficult due to high expression of multiple anti‐apoptotic proteins. Here, the authors tested the effectiveness of novel anti‐apoptotic protein MCL1 inhibitors against a large panel of melanoma lines and examined the potential to combine them with inhibitors of the BET protein family of epigenetic readers. The results show that combining BET and novel MCL1 inhibitors is highly effective at killing many melanoma cell lines by inducing a pro‐apoptotic state while also targeting MCL1. This novel treatment approach may benefit the large proportion of melanoma patients who fail current treatment with targeted therapies and/or immunotherapies.